Cue Reactivity in Nicotine and Alcohol Addiction: A Cross-Cultural View - Lv, Wanwan; Wu, Qichao; Liu, Xiaoming; Chen, Ying; Song, Hongwen; Yang, Lizhuang; Zhang, Xiaochu (Frontiers in Psychology, 2016)
A wealth of research indicates that cue reactivity is critical to understanding the neurobiology of nicotine and alcohol addiction and developing treatments. Functional magnetic resonance imaging (fMRI) and electroencephalograph (EEG) studies have shown abnormal cue reactivity in various conditions between nicotine or alcohol addicts and the healthy. Although the causes of these abnormalities are still unclear, cultural effect can not be ignored. We conduct an review of fMRI and EEG studies about the cue reactivity in nicotine and alcohol addiction and highlight the cultural perspective. We suggest that cultural cue reactivity is a field worth of exploring which may has an effect on addictive behavior through emotion and attention. The cultural role of nicotine and alcohol addiction would provide new insight into understanding the mechanisms of nicotine and alcohol addiction and developing culture-specific therapies. We consider that culture as a context may be a kind of factor that causes confusing outcomes in the research on nicotine and alcohol addiction which makes it possible to control the cultural influences and further contribute to the more consistent results.